2023
DOI: 10.3390/molecules28093664
|View full text |Cite
|
Sign up to set email alerts
|

New Indazol-Pyrimidine-Based Derivatives as Selective Anticancer Agents: Design, Synthesis, and In Silico Studies

Abstract: In this research study, the authors successfully synthesized potent new anticancer agents derived from indazol-pyrimidine. All the prepared compounds were tested for in vitro cell line inhibitory activity against three different cancerous cell lines. Results demonstrated that five of the novel compounds—4f, 4i, 4a, 4g, and 4d—possessed significant cytotoxic inhibitory activity against the MCF-7 cell line, with IC50 values of 1.629, 1.841, 2.958, 4.680, and 4.798 μM, respectively, compared to the reference drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…The predictive analysis and in silico studies of possible targets, ADME parameters (absorption, distribution, metabolism, and excretion), and compliance with the bioavailability criteria [ 11 , 22 ] were carried out for the studied compounds.…”
Section: Resultsmentioning
confidence: 99%
“…The predictive analysis and in silico studies of possible targets, ADME parameters (absorption, distribution, metabolism, and excretion), and compliance with the bioavailability criteria [ 11 , 22 ] were carried out for the studied compounds.…”
Section: Resultsmentioning
confidence: 99%
“…By studying the structures of previously reported kinase inhibitors, we found that the vast majority of these inhibitors possess pyrimidine as either 2-anilinopyridine or 2-anilinopyrimide as a pharmacophore in their structure [21][22][23][24][25][26][27]. In this study, we aimed to synthesize pyrimidine derivatives, either 2-aminopyrimidine or 2-anilinopyrimidine, with a different hydrophobic system (phenyl, pyridinyl, or pyrimidinyl) at position 4 of the pyrimidine ring, attached to either electron-withdrawing or electron-donating groups, which could affect the activity of the target compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, position 5 of the pyrimidine ring was designed to be occupied either by a proton or cyano group that was reported to be in contact with the gatekeeper residues, allowing the study of the structureactivity relationship of these compounds as effective antitumor candidates with potential CDK inhibitory activities (Figure 2). By studying the structures of previously reported kinase inhibitors, we found that the vast majority of these inhibitors possess pyrimidine as either 2-anilinopyridine or 2anilinopyrimide as a pharmacophore in their structure [21][22][23][24][25][26][27]. In this study, we aimed to synthesize pyrimidine derivatives, either 2-aminopyrimidine or 2-anilinopyrimidine, with a different hydrophobic system (phenyl, pyridinyl, or pyrimidinyl) at position 4 of the pyrimidine ring, attached to either electron-withdrawing or electron-donating groups, which could affect the activity of the target compounds.…”
Section: Introductionmentioning
confidence: 99%